Cultivating students' sustainability-oriented learning at the interface of science and society: a configuration of interrelated enablers. Issue 8 (15th July 2022) - Tassone, Valentina C.; den Brok, Perry; Tho, Cassandra W.S.; Wals, Arjen E.J.
Abstract : Purpose: By envisioning the learning environment as an eco-social system, this study aims to map interrelated enablers of students' sustainability-oriented learning (SoL) in the context of a university course at the interface of science and society. Design/methodology/approach: A case-study approach was used to delineate what enables student learning in a university-wide transdisciplinary Master of Science course. A sample of 102 students, university and societal stakeholders participated to this study, by sharing their experiences and views through focus groups and questionnaires. Findings: A main finding is the development of a configuration of six intertwined enablers that through their interplay help to cultivate students' SoL, in the course under exploration. Originality/value: This study paves the way for a re-orientation of how to explore learning in complex environments. It shows that adopting a relational, situated and systems approach is not only feasible but is also desirable to understand and guide learning practices in complex environments.